EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION AND AUTOGENIC ON REDUCING BLOOD GLUCOSE LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS - Mira Astri Koniyo; Rini Fahriani Zees; Lisdiyanti Usman (Universitas Negeri Gorontalo, 2021)
Diabetes Mellitus ( DM) is a group of metabolic diseases with hyperglycemia due to insulin abnormalities. The population in this study is Type 2 DM Sufferers who perform outpatients in puskesmas city north of Gorontalo city. This study aims to know the Effectiveness of the Muscle Relaxation Program ( PMR) and autogenic decrease blood glucose levels in DM Type 2 patients. Quasi-experimental research design with pre-experimental design two-group pre-post test design, namely researchers divided DM patients in group A. They gave progressive muscle relaxation interventions and group B autogenic therapy. Before the treatment has done, two groups measured blood glucose levels using the point care of testing method, then observed again by taking blood glucose measurements while after the two interventions. The sampling technique is purposive sampling. Based on Mann-Whitney's test analysis of the group of respondents given PMR (Progressive Muscle Relaxation) treatment and autogenic therapy to determine whether there was a significant difference between the post test scores in both groups, it is known that the probability value (sig) 0.05 (0.468 0.05), meaning that blood glucose when diabetic mellitus between the two groups there was no significant difference. It is concluded that effective progressive muscle relaxation and autogenic to decrease blood glucose levels in dm type 2 patients in the working area of the puskesmas city north of Gorontalo city.